"Hope Ambassadors" bring stories of recovery to Summit. Issue 17 (28th April 2023) - Knopf, Alison
Abstract : Carl Varney and Shannon Hall — two men from eastern Kentucky with severe opioid use disorder (OUD) in the past — praised their recovery at Teen Challenge, a Christian faith‐based, abstinence‐based treatment program. We don't hear enough about this aspect of treatment, which, although controversial because it is faith‐based and abstinence‐based and not welcome in many states, works for some people. Here is Varney's story, which he told to ADAW at the Rx and Illicit Drug Summit last month.